Logistics Operations Under Sanctions - Abu Ayash, Nada (2012)
This dissertation paper aims on understanding how the logistics & transport industry operates when it’s under the influence of political sanctions especially economic sanctions, and how various participants involved in this industry adapt to or embrace these changes. A broad review of existing literatures on both sanctions and logistics areas and related topics is conducted in order to understand the influence sanctions could have on the logistics operations. Afterwards, we discuss the potential effects of the various types of sanctions by classifying them according to the direct and indirect effects on the logistics operations. Finally, we analyze the changes that occur in the logistics & transport sector in light of some of its aspects. Also, in addition to the logistics operations in the target state, we expand our research by discussing the effects sanctions could cause on the logistics sector in the neighboring and third-party countries as well. The analysis and discussion of this paper is supported by various real life examples provided throughout the paper.